Pengaruh Kualitas Corporate Sosial Responbility,Good Corporate Governance,Dan Ceo Overcondence Terhadap Penghindaran Pajak - Sutiono Ono (Yayasan Literasi Ilmiah Indonesia, 2025)
Purpose : The purpose of this study is to prove the influence of corporate social responsibility quality, good corporate governance, and ceo overconfidence on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange Method: This research uses quantitative and secondary data sourced from the company's official website, as well as the Indonesia Stock Exchange (IDX) website. The technique used was purposive sampling using research subjects from manufacturing companies listed on the Indonesia Stock Exchange in 2022-2024. The sample data collected includes 192 manufacturing companies. Finding : Based on the research results,it show that CSR has a positive influence on tax avoidance,GCG has a positive influence on tax avoidance,and ceo overconfidence has a positive influence on tax avoidance in manufacturing company Novelty: This research is novel because the researchers added a new time period and sample determination.